Financial Implications of the Shrinking Supply of U.S. Treasury Securities - Schinasi, Garry (IMF Working Papers; Working Paper ;, 2001)
Recent improvements in fiscal positions in advanced countries have sharply curtailed the issuance of government securities and created the possibility that government securities could disappear in some countries. The possibility that this might occur in the United States has attracted the most attention, in large part because of the international role of the U.S. dollar and the widespread perception that U.S. treasury securities have the lowest total financial risk (the combination of credit, market, and liquidity risks) among U.S. dollar assets. This paper analyzes the unique features of government securities and links them to the important roles that government securities, in particular U.S. treasury securities, have come to play in national and international financial markets. The paper then identifies and examines financial market-oriented public policy questions raised by the shrinking supply of U.S. treasuries.